2023
DOI: 10.2147/ijn.s436111
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Conductive Hydrogel for Spinal Cord Injury Repair and Regeneration

Cheng Qin,
Zhiping Qi,
Su Pan
et al.

Abstract: Spinal cord injury (SCI) treatment represents a major challenge in clinical practice. In recent years, the rapid development of neural tissue engineering technology has provided a new therapeutic approach for spinal cord injury repair. Implanting functionalized electroconductive hydrogels (ECH) in the injury area has been shown to promote axonal regeneration and facilitate the generation of neuronal circuits by reshaping the microenvironment of SCI. ECH not only facilitate intercellular electrical signaling bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…Human tissue and organ regeneration capabilities are notably constrained, particularly following surgery, where tissue defects may result in delayed or non-healing wounds due to inadequate blood supply, as well as in the restoration and functional recovery of the central nervous system after injury. 694 , 695 Consequently, developing therapies aimed at replacing or repairing these damaged tissues has emerged as a critical focus within regenerative medicine. Hydrogels, among various materials utilized in tissue engineering and regenerative medicine, have become essential for regenerating diverse tissues, including skin, bone, and nerves.…”
Section: Hydrogels For Non-cell Therapymentioning
confidence: 99%
“…Human tissue and organ regeneration capabilities are notably constrained, particularly following surgery, where tissue defects may result in delayed or non-healing wounds due to inadequate blood supply, as well as in the restoration and functional recovery of the central nervous system after injury. 694 , 695 Consequently, developing therapies aimed at replacing or repairing these damaged tissues has emerged as a critical focus within regenerative medicine. Hydrogels, among various materials utilized in tissue engineering and regenerative medicine, have become essential for regenerating diverse tissues, including skin, bone, and nerves.…”
Section: Hydrogels For Non-cell Therapymentioning
confidence: 99%
“…Due to high electrical activity, such matrices promote cell adhesion, their growth and proliferation. Polypyrrole (PPy), polyaniline (PANi), polythiophene (PT), its derivatives, and poly (3,4-ethylenedioxythiophene) (PEDOT) are most often used for SC tissue regeneration ( Qin et al, 2023 ).…”
Section: Hydrogels and Spinal Cord Repairmentioning
confidence: 99%
“…In recent years, a large number of studies have been devoted to elucidating effectiveness of hydrogel matrices during implantation in the SCI area ( Lv et al, 2022 ; Radulescu et al, 2022 ; Qin et al, 2023 ; Sun et al, 2023 ). It was shown that hydrogels, as synthetic and semi-synthetic matrices, provide appropriate conditions for cell adhesion and cellular remodelling in a three-dimensional structure ( González-Díaz and Varghese, 2016 ; Akther et al, 2020 ; Ligorio and Mata, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…When injury occurs, the signaling pathway between afferent and efferent neurons is disrupted, preventing the normal transmission of electrical signals to the other side, and resulting in loss of motor function and abnormal sensory functions [20]. Benefiting from the progress of biomaterial scaffolds in nerve injury repair and nerve function regeneration, rational design of nerve regeneration scaffolds with electrical activity can not only mimic the electronic conductivity of the natural spinal cord, but also facilitate the delivery of drugs, cytokines, or cells to target sites [12,21]. Thus, the SCI-post microenvironment can be modulated, which would further promote the reconnection of the neural circuits interrupted by SCI, and facilitate neural regeneration [22][23][24].…”
Section: Introductionmentioning
confidence: 99%